Classification, technical efficiency, and economic performance of producers in the main productive region of quinoa in Peru - Mercado, Waldemar (2022)
Classifying small agricultural producers based on their technical efficiency and economic performance allows us to gauge the potential to improve yield in the quinoa crop, promote local food security, and improve rural incomes. Consequently, the objective of this study was to characterize and classify quinoa producers at the Peruvian Altiplano based on their productive, economic, and social attributes, so the technical efficiency and economic performance of the identified groups can be analyzed. Hence, 409 surveys conducted among quinoa producers in the Puno region were used to run the statistical analysis using two-stage cluster techniques, stochastic frontier, linear regression, and ANOVA tests. The results revealed that three groups of producers exhibited discriminating variables in the use of fertilizers, organic fertilizers, weed control, application of fungicides, production of quinoa, the total area of all crops, and achievement of economic benefits. It was evidenced that the use of seeds and fertilizers, in optimal quantities, increased yield, and in combination with quinoa sales, were the significant variables to differentiate technical efficiency. The high Andes are characterized by smallholdings, subsistence agriculture and, agrobiodiversity conservation and, although cultivation practices are predominantly low technical efficient, it would be possible to rapidly increase agricultural performance with a better allocation of external inputs. However, this could be done to regional limits, for this reason, the role of public policy is very important so that producers can get broader access to production inputs and technical services.